Enhancing eleventh graders’ speaking skill through communicative tasks based on storytelling and short performances at a public institution in Cimitarra, Santander in Colombia (2022)
Eng: In Colombia it is noticeable that despite the efforts of the National Ministry of Education, schools and teachers’ commitment to improve the teaching- learning practices of English as foreign language, the students are still having limitations at the moment of using the language in communicative contexts, and it is reflected, for instance on the results of the Pruebas Saber ICFES. As well, many times this is due to not only because of the language itself, but because it is necessary to implement other communicative strategies that enable the students to feel engaged with the language, and that at the same time can encourage them to use it in the contexts in which it is needed; which is mostly the classroom. Henceforth, in this qualitative research framed in an Action Research it was possible to document what the implementation of communicative tasks based on storytelling, music and short performances revealed about eleventh graders English speaking skill in a public institution in Cimitarra, Santander in Colombia. In order to provide an answer to the research question, seven Task- Based- Approach communicative tasks based on theater, music and storytelling were implemented. Video recordings and two interviews were used for data gathering. Findings revealed that these communicative tasks guided and helped students not only to improve their speaking skill but also their self-confidence at the moment of using the language in front of their partners. They also supported them to interact in a better way; likewise, encouraged and pushed them to express themselves, to use their imagination and put into practice not only their prior knowledge but also their autonomy and creativity.